Estimating syphilis seroprevalence among patients in a sexually transmitted infections clinic in Lilongwe, Malawi. (March 2020) - Chen, Jane S; Matoga, Mitch; Khan, Shiraz; Jere, Edward; Massa, Cecilia; Ndalama, Beatrice; Seña, Arlene C; Lancaster, Kathryn E; Hosseinipour, Mina C; Cohen, Myron S; Miller, William C; Hoffman, Irving F
The syndromic management of genital ulcer disease (GUD) misses asymptomatic syphilis cases but is widely utilized in resource-limited settings without diagnostic capabilities to ensure treatment for the most common etiologies of GUD. We used rapid serology tests for syphilis screening at a Malawian sexually transmitted infections clinic. The estimated seroprevalence was 9% and was highest among patients with genital ulcers (26%) and newly diagnosed HIV infection (19%). Rapid syphilis screening has the potential to increase syphilis detection, but accurate patient histories regarding syphilis diagnosis and prior treatment are needed.